Performing the City’s Urban Imaginary – the New Taipei City Museum of Art - Mersmann, Birgit (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
Aspiring global cities, such as Taipei City in Taiwan, seek to accumulate cultural capital. For future-oriented local and global self-representation, they design cutting-edge contemporary museums. This paper analyzes the “urban imaginary” as constructed by new urban museumscapes. Choosing a case-study approach, it explores the embedding of a vanguard art museum project in Taiwan – the New Taipei City Museum of Art in Taipei – into long-term urban planning strategies. In order to understand the purpose and process of how the new museum of contemporary art. is devised as a public space of cultural self-representation and urban identity building, the study monitors the complete design process from the city government’s urban and institutional planning strategy to the architectural design. Evidence shows that the pathways of urban place-making for art and through art and design in Taipei are strongly determined by the historical role and current geopolitical repositioning of the city.